Предмет: Математика,
автор: 8BlackFlash8
Помогите please я дам 30 баллов
Приложения:
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
используем два выражения
a³+b³=(a+b)(a²-ab+b²)
(a-b)²=a²-2ab+b²
(67^3+52^3) / 119-67 * 52 =(67+52)(67^2-67*52+52^2)/119 - 67*52= 119*(67^2-67*52+ 52^2)/119-67*52= 67^2-2*67*52+52^2=(67-52)^2=15^2=225
Похожие вопросы
Предмет: Алгебра,
автор: andrijopaec030
Предмет: Русский язык,
автор: oagata
Предмет: Математика,
автор: itachi7777ok
Предмет: Математика,
автор: ксюша1082
Предмет: Алгебра,
автор: gagyga